Preeclampsia and long-term coronary artery disease: How to minimize the odds?. (December 2020) - Oikonomou, P.; Tsonis, O.; Paxinos, A.; Gkrozou, F.; Korantzopoulos, P.; Paschopoulos, M.
Abstract: Preeclampsia (PE) is a hypertensive disorder of pregnancy that can cause detrimental obstetric outcomes if not managed properly. Current evidence demonstrates higher risk for long-term cardiovascular disease in preeclamptic women. Even in uncomplicated pregnancies, the heart work overload often reveals subtle cardiac defects or abnormalities, which otherwise remain undiagnosed in women without a history of pregnancy. Pathophysiologic patterns occurring in PE patients resemble biochemical responses observed in cases of cardiovascular disease. It has been estimated that women with an obstetric history of PE are more likely to develop coronary artery disease in the long run. Currently, additionally to whether any approach could actually contribute to minimizing mortality and morbidity among these affected populations, there is no consensus regarding management for these patients. In this review we summarized the current scientific evidence regarding the correlation between PE and long-term coronary artery disease. Based on this knowledge, we propose postpartum and lifetime management for these high-risk patients in order to minimize morbidity and mortality within this population.